Hemorheological study on erythrocyte aggregation in patients with type 2 diabetes mellitus without cholesterol and with hyper cholesterol - Babu, N. (Thrombosis update, 2021)
The aggregation of erythrocytes has been studied in many pathological conditions like diabetes mellitus, malaria, jaundice, hyper cholesterol, etc. Different types of erythrocyte aggregation occur in different pathological conditions. Enhanced aggregation was found in pathological conditions compared to control subjects. This research aims to study the aggregation of erythrocytes in type 2 diabetes mellitus subjects without cholesterol and with cholesterol and to compare such subjects with healthy subjects. Aggregation of erythrocytes was determined using an online erythrocyte aggregometer based on sequential analysis of transmitted laser light intensity after passing through the erythrocyte suspension in plasma. The aggregation mechanism was determined in terms of several aggregation parameters such as aggregation size index (ASI), aggregation sedimentation time index (ASTI), and the total number of fluctuations (TNF) of erythrocyte aggregates. These parameters were used to describe the dynamic nature of the aggregation process under gravitation quantitatively. There were a total of 45 subjects (control subjects (n = 10)), diabetes with normal cholesterol (n = 24), and diabetes with hyper cholesterol (n = 21) in this study. The aggregation parameter total number of fluctuations (TNF) was 1634 ± 397 in normal subjects, 1539 ± 197 in group 1, and 1096 ± 180 in group 2. The aggregation sedimentation time index (ASTI, Fig. 2) indicates the time taken by the aggregates to sediment (28–32 min for normal, 24–28 min for group 1, and 16–20 min for group 2 subjects). The aggregation parameters decreased in diabetes with normal cholesterol and were significantly decreased in diabetes with hyper cholesterol compared to controls. The results show that in patients with diabetes with normal cholesterol, the aggregation of erythrocytes is increased and in patients with diabetes with hyper cholesterol, the aggregation increased significantly. The significant increase in aggregation in diabetes with hypercholesterol may increase the microcirculatory complications compared to diabetes with normal cholesterol. •Aggregation of erythrocytes is important for the study of hemorheology.•Enhanced aggregation found in diabetes influences the flow properties of blood.•This aggregation is further enhanced if the complication of hyper cholesterol added in diabetes.•This study compares the main rheological property of erythrocyte aggregation in diabetes and hyper cholesterol patients.